Position of soils and soil-like formations of football grounds in the soil classification system - I. V. Zamotaev; V. P. Belobrov (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Under consideration is the classification of soils and soil-like formations in special landscapes and the football ground in particular. The latter is usually represented by soils subjected to human impacts of varying intensity: from weakly transformed by technogenic processes to artificial soils or technogenic superficial formations. The objects of research are more than 40 football grounds in Russia and the Republic of Byelarus. They differ in the age (exploitation time), regular and intensive technogenic loads, natural conditions and soil properties. The football grounds under study were divided into 3 groups: sports-ground at the age of its exploitation (less than 5 years), sports-mass grounds (30-50 years) and professional football grounds (50-75 years). Every group of football grounds is characteristic of soils and technogenic superficial formations represented by (1) technogenic-natural soils, (2) technogenically transformed soils and (3) technogenic superficial formations. The first two groups include the surface-transformed and disturbed soils, the natural profile of which is weakly changed. The technogenic superficial formations artificially constructed on the buried horizons of natural soils are highly subjected to technogenesis. In dependence on natural and technogenic conditions, age or exploitation time, peculiar features of soil stratum on football grounds it is possible to recognize a postlithogenic type of soddy-podzolic soils as well as 3 synlithogenic types represented by techno-soddy podzolic soil and 2 types of technogenic superficial formations including primitive and soddy quasizems. The evolution trends are striving to develop three subtypes of soddy quasizems under all the bioclimatic conditions including lessive, gleyic and solonetzic ones, whereas under humid conditions of the Moscow region there exist 5 subtypes of techno-soddy podzolic soils represented by lessive, gleyic, technogenically overcompacted, residual-carbonate and chemically polluted ones.